Anodization-free fabrication process for high-quality cross-type Josephson tunnel junctions based on a Nb/Al-AlOx/Nb trilayer - Adam, Fabienne; Enss, Christian; Kempf, Sebastian (Superconductor science and technology, 2024)
Josephson tunnel junctions form the basis for various superconductor electronic devices. For this reason, enormous efforts are routinely taken to establish and later on maintain a scalable and reproducible wafer-scale manufacturing process for high-quality Josephson junctions. Here, we present an anodization-free fabrication process for Nb/Al-AlO x /Nb cross-type Josephson junctions that requires only a small number of process steps and that is in general intrinsically compatible with wafer-scale fabrication. We show that the fabricated junctions are of very high quality and, compared to other junction types, exhibit not only a significantly reduced capacitance but also an almost rectangular critical current density profile. Our process hence enables the usage of low capacitance Josephson junctions for superconductor electronic devices such as ultra-low noise dc-superconducting quantum interference devices (SQUIDs), microwave SQUID multiplexers based on non-hysteretic rf-SQUIDs and RFSQ circuits.
Gesehen am 19.12.2024
Im Titel ist der Buchstabe "x" tiefgestellt